REPRESENTASI KESENJANGAN SOSIAL DALAM FILM PARASITE (ANALISIS SEMIOTIKA ROLAND BARTHES) - Patmawati Patmawati; Hamdan Hamdan; Masyhadiah Masyhadiah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study aims to identify the social inequality represented in the film Parasite. This research uses Roland Barthes' semiotic analysis method which consists of two stages of marking, namely denotation and connotation. Supporting data in this study uses literature study to obtain relevant theories and data that can be used to solve problems. The results showed that in denotation and connotation there is a meaning of social inequality in the Parasite film which is shown through several markers in the form of audio and visual. Forms of social inequality such as education inequality, inequality in living environment, gap of opportunity. Surrounding myths such as the myth of education fever and the sanpo generation. Meanwhile, the ideology that surrounds it is the ideology of individualism, which is delivered by the capitalist economic system.